2005
DOI: 10.1081/ss-200042517
|View full text |Cite
|
Sign up to set email alerts
|

Sorption Modeling of Strontium, Plutonium, Uranium, and Neptunium Adsorption on Monosodium Titanate

Abstract: We examined the ability of various equilibrium isotherms to replicate the available data for the adsorption of strontium (Sr), plutonium (Pu), uranium (U) and neptunium (Np) on monosodium titanate (MST) during the treatment of simulated and actual Savannah River Site high-level waste. The data comes from numerous experimental studies conducted between 1999 and 2002. The analysis considered 29 isotherm models from the literature. As part of this study, we developed a general method for selecting the best isothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Historical data suggests reasonable ability to predict actual waste performance based on these studies. 4 • The omission of sludge solids otherwise normally present in actual wastes (during the initial SWPF MST strike and MST reuse) will not cause the simulant waste to deviate substantially from the behavior of actual waste. Past experiments do indicate that sludge solids add complexity to the radionuclide behavior -and especially that of strontium -but with minor relative impact.…”
Section: Introductionmentioning
confidence: 99%
“…Historical data suggests reasonable ability to predict actual waste performance based on these studies. 4 • The omission of sludge solids otherwise normally present in actual wastes (during the initial SWPF MST strike and MST reuse) will not cause the simulant waste to deviate substantially from the behavior of actual waste. Past experiments do indicate that sludge solids add complexity to the radionuclide behavior -and especially that of strontium -but with minor relative impact.…”
Section: Introductionmentioning
confidence: 99%
“…al evaluated published isotherm models for the adsorption of Sr, Pu, Np, and U onto MST using experimental data collected from numerous tests at SRNL. 6 Of the 29 isotherm models investigated, the Dubinin-Astashov (DA) model provided good predictions for the adsorption of Sr and actinides with the fewest number of parameters and operations. Subsequently, Fondeur et.…”
Section: Strontium Plutoniummentioning
confidence: 99%
“…[19][20][21][22][23] Sorption of heavy metals and other nonradioactive metals found in industrial waste streams receives less attention, however, a number of examples can be found. Sorption of barium, chromium, mercury and zinc onto MST, [24][25][26] sorption of cadmium onto lithium, sodium, and potassium-titanates, [27,28] and sorption of copper, zinc, and nickel onto lithium-titanate are reported.…”
Section: Introductionmentioning
confidence: 99%